Logika Struktur Roman Arch dalam Kaitannya dengan Yesus Kristus sebagai Batu Penjuru - Gibbor Natanael Montolalu; John Abraham Steve Kalalo (LPPM STT Baptis Kalvari, 2023)
In the Book of Matthew, there are many parables that explain the Kingdom of Heaven that Jesus conveyed during his ministry. One of them is the parable of the Rented Vineyard. The important point in the parable is the explanation of Jesus Christ as the cornerstone. The purpose of this article is to understand the meaning conveyed in this parable through the philosophical meaning of Roman architecture, particularly in relation to the use of the cornerstone as one of its elements. This research was conducted by exploring the principles and logic of the Roman arch structure and its application to find a correct and precise conclusion about the meaning of the cornerstone. The hope is that the results of this research will lead to a deeper understanding of the will of God, especially the meaning of the Kingdom of Heaven that Jesus tried to convey through his quote.